Research on the Application of Intelligent Education Products in Education and Teaching - Xuan, Zhou (Proceedings of International Conference of Educational Innovation through Technology (Online), 2023)
This study combs the mainstream intelligent education products on the market from four aspects: teaching application, learning application, management application, and evaluation application. In terms of teaching application, the relevant intelligent education products are divided into four categories: online education intelligent education products, all-subject intelligent education products, sub-subject intelligent teaching products, and special intelligent education products. In terms of learning applications, related intelligent education products are classified into four categories: adaptive learning, assisted answering, intelligent practice, and graded reading. The research focuses on the functions and values of each type of intelligent education product, summarizing the impact of intelligent education products on education and teaching as well as the challenges they face.